Neutrophil Extracellular Traps Tied to Rheumatoid Arthritis: Points to Ponder - Song, Wenpeng; Ye, Jing; Pan, Nanfang; Tan, Chunyu; Herrmann, Martin (Frontiers in Immunology, 2021)
In recent years, neutrophil extracellular traps at the forefront of neutrophil biology have proven to help capture and kill pathogens involved in the inflammatory process. There is growing evidence that persistent neutrophil extracellular traps drive the pathogenesis of autoimmune diseases. In this paper, we summarize the potential of neutrophil extracellular traps to drive the pathogenesis of rheumatoid arthritis and experimental animal models. We also describe diagnosis and treatment of rheumatoid arthritis in association with neutrophil extracellular traps.